THE CHALLENGE OF LEARNING TOURISM ONLINE DURING A PANDEMIC: STUDENTS’ VIEWPOINT - Bagus Reza Hariyadi; Yuni Astuti; Dian Bayu Firmansyah (Universitas Sahid, 2023)
The impact of the COVID-19 outbreak has caused every college and school to stop offline learning activities. For one year, online tourism learning has become a learning option, as well as a new challenge for students and lecturers. This study aims to find out the problems and challenges faced by students during online tourism learning during the pandemic. Respondents from this study were 67 students who took tourism courses. The results showed that students experienced a number of difficulties during online learning such as signal difficulties, lack of motivation to study, difficulty concentrating, and difficulties in practicing tour guiding online. The positive sides of online learning include; unlimited distance, prevent the transmission of the covid-19 virus, no need to meet in person. Overall, students prefer offline tourism learning compared to online learning due to the difficulties they face during the implementation of online learning. It is hoped that lecturers can convey interesting methods and techniques in online tourism teaching to boost student motivation and performance to study tourism in this pandemic situation.